2018
DOI: 10.3389/fnhum.2018.00281
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Assessing the Flexible Acquisition, Integration, and Deployment of Human Spatial Representations and Information

Abstract: Studying human spatial navigation in the lab can be challenging, particularly when including non-invasive neural measures like functional magnetic resonance imaging (fMRI) and scalp encephalography (EEG). While there is broad consensus that human spatial navigation involves both egocentric (self-referenced) and allocentric (world-referenced) coding schemes, exactly how these can be measured in ecologically meaningful situations remains controversial. Here, we explore these two forms of representation and how w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 58 publications
(83 reference statements)
2
21
1
Order By: Relevance
“…S70 Demonstrating the measured memory performance is elevated in AR and that subjects subjectively prefer AR over VR in terms of difficulty, immersion and enjoyment is the main result of this project, indicating that assessing spatial memory in AR is at least as valid, if not significantly better, then VR. Whereas previous VR memory paradigms had been criticized because memory performance was lower compared to real-world spatial memory [30], our results show that AR helps address this gap. Subjects showed significant spatial memory in all 4 conditions.…”
Section: Comparing Ar and Vrcontrasting
confidence: 58%
See 4 more Smart Citations
“…S70 Demonstrating the measured memory performance is elevated in AR and that subjects subjectively prefer AR over VR in terms of difficulty, immersion and enjoyment is the main result of this project, indicating that assessing spatial memory in AR is at least as valid, if not significantly better, then VR. Whereas previous VR memory paradigms had been criticized because memory performance was lower compared to real-world spatial memory [30], our results show that AR helps address this gap. Subjects showed significant spatial memory in all 4 conditions.…”
Section: Comparing Ar and Vrcontrasting
confidence: 58%
“…The use of these setups has been compared to traditional screen-based desktop VR. This line of work has shown general equivalence between the methods, with various advantages to walking over stationary conditions [23,26,27,28,30]. From the neuroscience perspective, it has been suggested that naturalistic head movements may sufficient to elicit natural spatial signals in VR that might be missing in fully virtual paradigms [2].…”
Section: Related Workmentioning
confidence: 97%
See 3 more Smart Citations